(untitled) (New York, 2004)
Video Aided Instruction's English Grammar Series makes the tricky rules of English grammar easier to learn than ever before - whether you're new to English or you've been speaking it for years! Perfect for classroom use or self-study, this program uses easy-to-follow examples and practice exercises from everyday life to help you master even the most complicated English grammar topics! It's also great for reviewing forgotten grammar or preparing for many verbal standardized exams such as the SAT, TOEFL, GED, and GRE. Plus, it can really help you improve your grades in school or advance your career! When you use a consistent grammatical pattern to link related gerunds, infinitives, and verbs in your sentences, you're using parallel structure. This important device helps you avoid clumsy sentence construction that can confuse and distract your audience.
Keywords: Tiếng Anh,English language; Ngữ pháp,Grammar